Hacker of visual memory, Minerva Cuevas - Mercado, Raquel (Facultad de Ciencias Políticas y Sociales, 2021)
This paper presents an analysis of the artistic practice of Minerva Cuevas, specifically the way in which her practice hacks the visual memory through strategies of repetition of the corporate discourse to criticize exploitative practices. The article shows the process of conceptualization of the artist's pieces, making use of the interview and the files of the analyzed pieces. Products, services, campaigns are part of the way in which Cuevas' artistic practice shows the relationships between social conflicts, government and corporate corruption.